2002
DOI: 10.1038/sj.jhh.1001315
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an ACE inhibitor and calcium antagonist on microalbuminuria and lipid subfractions in type 2 diabetes: a randomised, multi-centre pilot study

Abstract: Background: Microalbuminuria (MA) is associated with increased cardiovascular risk and lipid abnormalities in people with type 2 diabetes. ACE inhibitors and calcium channel blockers (CCBs) reduce MA and are neutral on total cholesterol and triglycerides. The effect of ACE inhibitors and CCBs on lipid subfractions such as Lp(a), apolipoprotein (apo) A1, apo B, and others, however, is unclear. The current study tests the hypothesis that a fixed-dose combination of an ACE inhibitor, benazepril (B) with the dihyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 43 publications
1
26
0
Order By: Relevance
“…Benazepril alone or in combination with amlodipine significantly increased HDL-C levels and decreased lipoprotein (a) levels compared with amlodipine monotherapy in 27 patients with type 2 diabetes after 36 weeks of treatment. 24 The increase in TG-rich lipoproteins as reflected by the increase in VLDL-C concentration may be the major mechanism to explain the redistribution of LDL-C from larger to sdLDL particles in the V --H group. Overproduction of large TG-rich VLDL particles could serve as a substrate for the production of sdLDL subfractions.…”
Section: Antihypertensive Combinations and Lipoprotein Subfractionsmentioning
confidence: 96%
See 2 more Smart Citations
“…Benazepril alone or in combination with amlodipine significantly increased HDL-C levels and decreased lipoprotein (a) levels compared with amlodipine monotherapy in 27 patients with type 2 diabetes after 36 weeks of treatment. 24 The increase in TG-rich lipoproteins as reflected by the increase in VLDL-C concentration may be the major mechanism to explain the redistribution of LDL-C from larger to sdLDL particles in the V --H group. Overproduction of large TG-rich VLDL particles could serve as a substrate for the production of sdLDL subfractions.…”
Section: Antihypertensive Combinations and Lipoprotein Subfractionsmentioning
confidence: 96%
“…31 However, 36-week treatment with benazepril or amlodipine alone or in combination did not significantly change LDL particle size in 27 patients with type 2 diabetes. 24 Thiazides normally exhibit a neutral effect on HDL-C levels with few reports of a slight decrease. 20,32 ARBs also seem not to exert significant alterations in HDL-C levels with the exception of reports showing a mild increase.…”
Section: Antihypertensive Combinations and Lipoprotein Subfractionsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table 1, about 69% of patients were prescribed ACE inhibitors as a discharge medication. Several studies have shown a relationship between ACE inhibitors and the lipid profile, especially the atherogenic index [13]. We then, analyzed the groups of patients separately according to ACE inhibitor usage to investigate whether these drugs had an impac on Comparison between patients with low, middle, and high tertile of TG/HDL-C ratio.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…A common mediator of end-organ damage in both hypertension and DM seems to be the Renin Angiotensin Aldosterone System (RAAS), and blockade of the RAAS therefore offers protection not only for BP reduction, but also for reducing end-organ damage in subjects with DM. 14 There are also beneficial effects of combination therapy in comparison with the individual drugs alone, 15,16 and the enthusiasts would strenuously argue that ACE inhibitors have advantageous effects on the development of diabetic complications beyond their BP-lowering effects. 17,18 Indeed, combination therapy with angiotensin II receptor blockers (ARB) and an ACE inhibitor has been advocated in hypertension, not only in the presence of DM 19,20 but also in the absence of DM.…”
mentioning
confidence: 99%